2023
DOI: 10.4149/gpb_2023012
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic model based on gene biomarkers for Crohn’s disease

Abstract: Crohn's disease (CD) is a segmental chronic inflammatory bowel disease, which seriously affects the patient's quality of life. The etiology of CD is not yet clear, and there is still a lack of effective treatments. Therefore, in this study, we focus on developing a useful model for early diagnosis and targeted therapy of CD. The expression datasets of CD were collected to filter differentially expressed genes (DEGs) by overlapping "limma" package and "WGCNA" package. Then, functional enrichment analysis and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
3
0
0
Order By: Relevance
“…In one scenario, stool MMP12 significantly discriminated pediatric UC and CD patients from healthy individuals [ 22 ]. Similarly, our results, along with previous observations [ 18 , 19 , 27 ], also confirmed the elevated expression of MMP12 in the intestinal mucosa of adult patients with UC and CD. Likewise, we demonstrated that the colonic expression of this metalloproteinase was strongly associated with the activity of the disease and the response to biological therapies.…”
Section: Discussionsupporting
confidence: 92%
“…In one scenario, stool MMP12 significantly discriminated pediatric UC and CD patients from healthy individuals [ 22 ]. Similarly, our results, along with previous observations [ 18 , 19 , 27 ], also confirmed the elevated expression of MMP12 in the intestinal mucosa of adult patients with UC and CD. Likewise, we demonstrated that the colonic expression of this metalloproteinase was strongly associated with the activity of the disease and the response to biological therapies.…”
Section: Discussionsupporting
confidence: 92%
“…IL1B had the highest score in hub genes ranked by MCC method in both psoriasis and IBD in this research, which is consonant with the conclusions expressed by Wu et al 33 IL1B was also the hub gene of CD in the research constructed by da Costa et al 34 An increased IL1B gene expression was detected in affected-skin psoriasis, when compared to control skin and non-affected skin psoriasis (p < 0.001). 34 GO and KEGG enrichment analysis indicated that the co-DEGs of psoriasis and IBD were mainly associated with response to lipopolysaccharide, secretory granule lumen, cytokine activity, and IL-17 signaling pathway.…”
Section: Discussionsupporting
confidence: 90%
“…IL1B had the highest score in hub genes ranked by MCC method in both psoriasis and IBD in this research, which is consonant with the conclusions expressed by Wu et al. 33 IL1B was also the hub gene of CD in the research constructed by da Costa et al. 34 An increased IL1B gene expression was detected in affected‐skin psoriasis, when compared to control skin and non‐affected skin psoriasis ( p < 0.001).…”
Section: Discussionsupporting
confidence: 90%